A feasibility study of a portable intraoperative specimen imaging X‐ray system based on carbon nanotube field emitters. Issue 3 (21st May 2021) - Gupta, Amar Prasad; Yeo, Seung Jun; Mativenga, Mallory; Jung, Jaeik; Kim, Wooseob; Lim, Jongmin; Park, Junyoung; Ahn, Jeung Sun; Kim, Seung Hoon; Chae, Moon Shik; Yeon, Yeong Heum; Kim, Namkug; et al.
Abstracts: When breast cancer is surgically removed, a rim of normal tissue surrounding the tumor is also removed. This rim of normal tissue is called a margin and is studied by a pathologist to determine whether or not all tumor was removed. The pathologist achieves this by cutting the surgically removed tissue into thin slices and observing each slice under a microscope. This process is time‐consuming. Here, we investigate the feasibility of using a portable carbon nanotube (CNT)‐based X‐ray system for in situ detection of the presence of tumor cells in the surgical margin. Using the proposed technique, we successfully obtain X‐ray images, which clearly show cancer masses and microcalcifications. This feasibility study shows that portable CNT‐based X‐ray systems are promising candidates for next‐generation in situ pathological examinations.